2022
DOI: 10.1016/j.ijom.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment and ear anomalies in craniofacial microsomia: a systematic review

Abstract: The aim of this systematic review was to review the literature on hearing impairment and ear anomalies in patients with craniofacial microsomia and to determine their prevalence. Sixty-two records including 5122 patients were included. Ear anomalies were present in 52-100% of patients. The most reported external ear malformations were microtia, pre-auricular tags, and atresia of the external auditory canal. Ossicular anomalies were the most reported middle ear malformations, whereas the most reported inner ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…HFM incidence varies widely in reports, ranging from 3000 to 26,000 individuals with an estimated occurrence of one. 1,3,15,18,19 No significant gender difference exists, with a male-to-female ratio of 1.09:1. 20 Although HFM is a common congenital anomaly, treatment approaches vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…HFM incidence varies widely in reports, ranging from 3000 to 26,000 individuals with an estimated occurrence of one. 1,3,15,18,19 No significant gender difference exists, with a male-to-female ratio of 1.09:1. 20 Although HFM is a common congenital anomaly, treatment approaches vary widely.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CFM may present with microtia or anotia, atresia of the external auditory canal, or dysplasia of the ossicular chain. 3 Scholars have reported that the incidence of inner ear malformations in CFM ranges from 8–36% 13,14 and includes cochlear dysplasia, dysplasia or absence of semi-circular canals, an enlarged vestibular aqueduct, and internal auditory canal stenosis. The internal carotid artery and facial nerve, which pass through the temporal bone, are also abnormal in some patients 15, 16 This study assessed the bilateral differences in anatomical landmarks on the temporal bone (including the inner ear) in a reconstructed 3D coordinate system.…”
Section: Discussionmentioning
confidence: 99%
“…2 Many structures of the temporal bone, such as the glenoid fossa and zygomatic arch, are malformed or absent on the affected side of patients with CFM. Existing research has described middle ear or inner ear malformations qualitatively 3 or compared the difference in skull base between the affected and unaffected sides of patients with CFM, describing the petromastoid part of the temporal bone two-dimensionally 4,5, 6 Considering that the alteration of bony structures in patients with CFM is three-dimensional (3D), 7 an accurate evaluation of temporal bone morphology will deepen the understanding of CFM skeletal deformities and may offer implications for its pathogenesis. Malformation of the zygomatic arch leads to depression and distortion of the face on the affected side, which affects aesthetic appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Much is known about the adverse effects of hypoplasia and asymmetry present in CFM on hearing, breathing, chewing, and swallowing. These effects include hearing loss in over 50% of individuals ( Rooijers et al, 2022 ), chewing and swallowing disorders in over 25%, and obstructive sleep apnea in up to 18% of children with CFM ( Caron et al, 2018 ; Caron, Pluijmers, Maas, et al, 2017 ). In contrast, information regarding the prevalence, etiology, and severity of speech disorders in CFM is limited ( Ronde et al, 2023 ).…”
mentioning
confidence: 99%